HUBUNGAN ANTARA JUMLAH KOLONI BAKTERI STREPTOCOCCUS MUTANS SALIVA DENGAN INDEKS KARIES (DMF-T) - Wulandari Wulandari; Widodo Widodo; Isnur Hatta (Dentin, 2022)
ABSTRACTBackground: The oral cavity is the second largest colony place for microbes in the body. One of the pathogenic bacteria in the oral cavity is Streptococcus mutans, has an important role in the occurrence of dental caries because it is acidogenic. Streptococcus mutans is able to attach to all surfaces of the oral cavity with the help of salivary pellicle. An increase in the number of Streptococcus mutans bacterial colonies in saliva is directly related to the degree of tooth decay. The degree of tooth decay in the oral cavity can be assessed using the DMF-T  caries index. Objective: To determine the relationship between the number of Streptococcus mutans bacteria colonies in saliva and the caries index (DMF-T) based on published research results. Methods: The review was conducted on 15 journals assessed according to inclusion criteria, such as being available in full-text form and relating to the relationship between the number of salivary Streptococcus mutans bacteria colonies and the caries index (DMF-T). Results: Based on 15 articles that have been reviewed, it was found that 13 articles (86.6%) stated that there was a relationship between the number of salivary Streptococcus mutans bacteria colonies with caries index (DMF-T) and 2 articles (13.4%) stated no there was a relationship between the number of salivary Streptococcus mutans with caries index (DMF-T). Conclusion: There is a correlation that tends to be directly proportional to the number of Streptococcus mutans bacteria colonies in saliva and the DMF-T caries index. Keywords: DMF-T index, Saliva, Streptococcus mutans. ABSTRAK Latar Belakang: Rongga mulut merupakan tempat berkumpulnya mikroba terbesar kedua dalam tubuh. Bakteri patogen dalam rongga mulut salah satunya adalah Streptococcus mutans, berperan penting dalam terjadinya karies karena bersifat asidogenik. Bakteri Streptococcus mutans mampu melekat disemua permukaan rongga mulut dengan bantuan pelikel saliva. Peningkatan jumlah koloni bakteri Streptococcus mutans dalam saliva berhubungan langsung dengan tingkat kerusakan gigi. Tingkat kerusakan gigi dalam rongga mulut dapat dinilai menggunakan indeks karies DMF-T. Tujuan: Mengetahui hubungan antara jumlah koloni bakteri Streptococcus mutans dalam saliva dengan indeks karies (DMF-T) berdasarkan hasil penelitian yang telah dipublikasi. Metode: Review dilakukan pada 15 jurnal yang dinilai sesuai dengan kriteria inklusi, seperti tersedia dalam bentuk full-text dan berkaitan dengan hubungan antara jumlah koloni bakteri Streptococcus mutans dalam saliva dengan indeks karies (DMF-T). Hasil: Berdasarkan 15 artikel yang telah dilakukan telaah, didapatkan sebanyak 13 artikel (86,6%) yang menyatakan bahwa terdapat hubungan antara jumlah koloni bakteri Streptococcus mutans dalam saliva dengan indeks karies (DMF-T) dan 2 artikel (13,4%) menyatakan tidak terdapat hubungan antara jumlah koloni bakteri Streptococcus mutans dalam saliva dengan indeks karies (DMF-T). Kesimpulan: Terdapat kecenderungan hubungan yang berbanding lurus antara jumlah koloni bakteri Streptococcus mutans dalam saliva dengan indeks karies DMF-T. Kata kunci: Indeks DMF-T, Streptococcus mutans, saliva.